Fraude à lei - NOBRE JÚNIOR, EDILSON PEREIRA (Revista da AJURIS - Qualis A2, 2014)
Este artigo objetiva analisar o instituto da fraude à lei, discorrendo não somente sobre os seus aspectos gerais, mas principalmente quanto à sua previsão pelo sistema jurídico brasileiro, seus efeitos e campo de aplicação. ABSTRACT: This article aims to analyze the institute of the circumvention of the law, discoursing not only about the general aspects, but mainly regarding to its prediction by the brazilian legal system, as well as its effects and field of application.